2011
DOI: 10.1088/1742-5468/2011/10/p10010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of linear and nonlinear time-delayed feedback on the noise-enhanced stability phenomenon in a periodically driven bistable system

Abstract: We investigate numerically the effects of time delay on the phenomenon of noise-enhanced stability (NES) in a periodically modulated bistable system. Three types of time-delayed feedback, including linear delayed feedback, nonlinear delayed feedback and global delayed feedback, are considered. We find a non-monotonic behaviour of the mean first-passage time (MFPT) as a function of the delay time τ, with a maximum in the case of linear delayed feedback and with a minimum in the case of nonlinear delayed feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The role of both noise sources on the mean escape time from the metastable state is studied. We find a nonmonotonic behavior with a maximum of the mean escape time as a function of both noise intensities, revealing the presence of the noise enhanced stability effect [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18]. (ii) The influence of non-Gaussian noise on the transient dynamics of a short overdamped Josephson junction, in the framework of the resistively shunted junction model and in the presence of a periodic driving, is investigated.…”
Section: Introductionmentioning
confidence: 94%
“…The role of both noise sources on the mean escape time from the metastable state is studied. We find a nonmonotonic behavior with a maximum of the mean escape time as a function of both noise intensities, revealing the presence of the noise enhanced stability effect [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18]. (ii) The influence of non-Gaussian noise on the transient dynamics of a short overdamped Josephson junction, in the framework of the resistively shunted junction model and in the presence of a periodic driving, is investigated.…”
Section: Introductionmentioning
confidence: 94%
“…Several theoretical studies have shown that the average escape time from metastable states in the presence of fluctuating and static potentials is characterized by nonmonotonical behavior with respect to the noise intensity [14,23,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. This resonance-like behavior, called noise enhanced stability (NES), is in contrast with the monotonic behavior predicted by Kramers theory [68,69]: the stability of metastable or unstable states is in fact enhanced by the noise with the average lifetime resulting larger than the deterministic one.…”
Section: Introductionmentioning
confidence: 95%
“…In particular, the escape time from the metastable well shows a nonmonotonic behavior, with a maximum, as the damping strength increases. This indicates that for a suitable value of the damping strength the escape time takes on a maximum value, which corresponds to a stabilization of the quantum system, a phenomenon which can be named quantum noise enhanced stability (qNES), according to the analogous effect observed in classical physics [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 25 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. This indicates that, contrary to the result predicted by Kramers [ 64 , 65 ], the average lifetime of a particle, initially placed in a metastable or unstable state, can be enhanced respect to the deterministic one [ 13 , 52 ].…”
Section: Introductionmentioning
confidence: 99%